NEGATIVE TRANSGRESSION AND ONTOGENETIC HUMAN SAFETY - Edward Karczewski (Defence Science Review, 2016)
This article indicates the role and importance of the transgression in the ontogenetic human development. It represents the attempt to show some the risks and the dangers arising by excessive and destructive crossing the borders of his achievements.